ZnSe Nanowires: Guided Growth of Horizontal ZnSe Nanowires and their Integration into High‐Performance Blue–UV Photodetectors (Adv. Mater. 27/2015). (July 2015) - Oksenberg, Eitan; Popovitz‐Biro, Ronit; Rechav, Katya; Joselevich, Ernesto
<x xml:space="preserve">Abstract</x> Guided growth of horizontally aligned semiconductor nano‐wires is a proven promising approach for their large‐scale integration into electronic and optoelectronic devices. However, this approach has so far only been demonstrated for semiconductors with bandgap energies in the UV and IR ranges. On page 3999, E. Joselevich and co‐workers demonstrate the guided growth of ZnSe nanowires with controlled structure and orientation, and their integration into visible light detectors.